ICC 2019 - 2019 IEEE International Conference on Communications (ICC) 2019
DOI: 10.1109/icc.2019.8761478
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Throughput Maximization in LoRa Networks Powered by Ambient Energy Harvesting

Abstract: In this paper, we investigate the uplink transmissions in low-power wide-area networks (LPWAN) where the users are self-powered by the energy harvested from the ambient environment. Demonstrating their potential in supporting diverse Internet-of-Things (IoT) applications, we focus on long range (LoRa) networks where the LoRa users are using the harvested energy to transmit data to a gateway via different spreading codes. Precisely, we study the throughput fairness optimization problem for LoRa users by jointly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…From the simulation results, it is shown that the proposed mechanism improves the fairness, data rates, and throughput performance when compared to the baseline algorithms. In [116], a resource allocation algorithm for LoRaWAN is introduced, which involves energy harvesting. The authors also provide a model to optimize SF allocation, energy harvesting duration and power devices for IoT transmission.…”
Section: B Sensor/iot Device Side 1) Resource Allocationmentioning
confidence: 99%
“…From the simulation results, it is shown that the proposed mechanism improves the fairness, data rates, and throughput performance when compared to the baseline algorithms. In [116], a resource allocation algorithm for LoRaWAN is introduced, which involves energy harvesting. The authors also provide a model to optimize SF allocation, energy harvesting duration and power devices for IoT transmission.…”
Section: B Sensor/iot Device Side 1) Resource Allocationmentioning
confidence: 99%
“…Benkhelifa et al [94] designed a resource allocation algorithm for LoRaWAN, which involved energy harvesting. The authors also developed a model to optimize the SF assignment, energy harvesting time duration, and power devices for IoT transmission.…”
Section: Multiple Parametermentioning
confidence: 99%
“…Benkhelifa el al. studied in Reference [ 1 ] the resource allocation in LoRa networks supplied by ambient energy harvesting. Mabon et al presented in Reference [ 25 ] a prototype of an energy harvesting LoRa platform with an accurate sizing of both the solar cell and the battery.…”
Section: Related Workmentioning
confidence: 99%
“…Such technology offers a link range of several kilometers and a low power consumption, but at the cost of small data rate. Many technologies belong to LPWAN category, such as SigFox, Narrowband IoT, Weightless, and LoRa [ 1 ]. Among these existing LPWANs sets, LoRa is the most popular due to its open communication protocol (LoRaWAN) and its ability to achieve a long range and to recover data from weak signals even below the noise floor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%